Practicing ethnography in law : - Starr, June (Palgrave Macmillan, 2002)
Starr (formerly of the Indiana U. School of Law) and Goodale (anthropology, Emory U.) present 11 papers that discuss the application of anthropological ethnography methods to the analysis of legal disputes, structures, and cultures. The papers consider methods of participatory research, discuss fieldwork in a variety of settings, and explore some conceptual problems. The two concluding essays explore larger issues of the practice and understanding of legal ethnography.